Critical Streptococcus suis Virulence Factors: Are They All Really Critical?. Issue 7 (July 2017) - Segura, Mariela; Fittipaldi, Nahuel; Calzas, Cynthia; Gottschalk, Marcelo
Abstract : Streptococcus suis is an important swine pathogen that can be transmitted to humans by contact with diseased animals or contaminated raw pork products. This pathogen possesses a coat of capsular polysaccharide (CPS) that confers protection against the immune system. Yet, the CPS is not the only virulence factor enabling this bacterium to successfully colonize, invade, and disseminate in its host leading to severe systemic diseases such as meningitis and toxic shock-like syndrome. Indeed, recent research developments, cautiously inventoried in this review, have revealed over 100 'putative virulence factors or traits' (surface-associated or secreted components, regulatory genes or metabolic pathways), of which at least 37 have been claimed as being 'critical' for virulence. In this review we discuss the current contradictions and controversies raised by this explosion of virulence factors and the future directions that may be conceived to advance and enlighten research on S. suis pathogenesis. Trends: Streptococcus suis is a major swine pathogen – an emerging zoonotic agent whose pathogenesis of disease is partially characterized. S. suis is an encapsulated microorganism and its capsular polysaccharide (CPS) allows bacterial evasion of the host immune system and bloodstream dissemination. But, the CPS is not the only virulence factor and, under certain circumstances, its absence may also be beneficial to pathogenic strains. Indeed, the immune-pathogenesis of S. suis -induced disease is a complex, multifactorial process. Yet, the discovery of a large array of virulence factors claimed as 'critical' for the pathogen's virulence has brought confusion into the field of S. suis . The large genetic diversity of the S. suis species further complicated the study of the pathogenesis of the disease.